Papa Does Preach: Daughters and Polarisation of Attitudes toward Abortion - Clémentine Van Effenterre (Institute of Labor Economics (IZA), 2017)
This article examines the hypothesis that having daughters polarises male politicians' attitudes toward abortion rights. Using French and U.S voting records, I estimate that having daughters decreases support for abortion law by 25% for right-wing congressmen in France, and increases support for Democrats by 12%. I find similar behavioural patterns for voters using electoral surveys. Robustness checks confirm that this result is not an artefact of family stopping rules. I rationalise these findings in a model predicting that fathers with paternalistic preferences adopt a more polarised political position on abortion when they have a daughter rather than a son.
Keywords: D72; D83; J16; 330; voting; polarisation; gender; political behaviour; attitudes; abortion